Extracellular CIRP Induces Macrophage Extracellular Trap Formation Via Gasdermin D Activation - Lee, Yongchan; Reilly, Bridgette; Tan, Chuyi; Wang, Ping; Aziz, Monowar (Frontiers in Immunology, 2021)
Extracellular cold-inducible RNA-binding protein (eCIRP) is a damage-associated molecular pattern promoting inflammation and tissue injury. During bacterial or viral infection, macrophages release DNA decorated with nuclear and cytoplasmic proteins known as macrophage extracellular traps (METs). Gasdermin D (GSDMD) is a pore-forming protein that has been involved in extracellular trap formation in neutrophils. We hypothesized that eCIRP induces MET formation by activating GSDMD. Human monocytic cell line THP-1 cells were differentiated with phorbol 12-myristate 13-acetate (PMA) and treated with recombinant murine (rm) CIRP. The MET formation was detected by three methods: time-lapse fluorescence microscopy (video imaging), colorimetry, and ELISA. Cleaved forms of GSDMD, and caspase-1 were detected by Western blotting. Treatment of THP-1 cells with rmCIRP increased MET formation as revealed by Sytox Orange Staining assay in a time- and dose-dependent manner. METs formed by rmCIRP stimulation were further confirmed by extracellular DNA, citrullinated histone H3, and myeloperoxidase. Treatment of THP-1 cells with rmCIRP significantly increased the cleaved forms of caspase-1 and GSDMD compared to PBS-treated cells. Treatment of macrophages with caspase-1, and GSDMD inhibitors z-VAD-fmk, and disulfiram, separately, significantly decreased rmCIRP-induced MET formation. We also confirmed rmCIRP-induced MET formation using primary cells murine peritoneal macrophages. These data clearly show that eCIRP serves as a novel inducer of MET formation through the activation of GSDMD and caspase-1.